Pengaruh Ragi Saccharomyces Cerevisiae dalam Pakan Komersial Terhadap Pertumbuhan Ikan Nila (Oreochromis niloticus) - Wardha Jalil (AquaMarine (Jurnal FPIK UNIDAYAN ), 2022)
Utilization of various types of feed raw materials that have good nutritional value is an important part of fish farming activities. One type of raw material for fish feed, namely yeast (Saccharomyces Cerevisiae), has the potential as an immunostimulant to accelerate the growth of tilapia (Oreochromis niloticus). This study aims to determine the growth of tilapia (O. niloticus) by adding yeast Saccharomyces cerevisiae to tilapia (O. niloticus) commercial feed. The research was conducted for 60 days, at the Fish Seed Production Laboratory, Aquaculture Program, Faculty of Fisheries and Marine Sciences, Dayanu Ikhsanuddin University, Baubau. The test feeds used were the yeast Saccharomyces Cerevisiae and the commercial feed FF-999. The organism were tilapia (O niloticus) 5 – 7 cm measuring, in an aquarium 50 cm x 30 cm x 35 cm with a density of 10 individuals. The research design used a Completely Randomized Design, 4 treatments and 3 replications. The treatments consisted of treatments A (0% yeast), B (2% yeast), C (4% yeast) and D (6% yeast). The results showed that the highest absolute growth of tilapia occurred in treatment D (6% yeast) of 24.02 ± 1.64 grams and the lowest absolute growth in treatment B (2% yeast) namely 17.81 ± 1.84 grams. The best feed conversion in treatment D (6% yeast) was 2.49 ± 0.30. The highest survival rate was in C treatment (4% yeast) and D treatment (6% yeast), namely 93.33%. Based on the results of the analysis of variance, the addition of yeast to the feed affected the growth of tilapia (P<0.05). However, it had no effect on feed conversion and survival rate of tilapia (P>0.05).